Doprowadź do najprostszej postaci.
a) -(8a-4b+5)+(-6a+2b-5)+3(a-b+1)=
b)3(a+2b-3c)+7(2a-4b+5c)-5(-3a-4b-5c)=
c)-4(-2x+6y+5z)-8(9x+8y-7z)+5(3x-6y+9z)=
d)(dwie trzecie) (3a+6b-12c)+(trzy piąte) (10a-15b+20c)-0,5(16a+24b-36c)=

Proszę serdeczne o pomoc na jutro ;(

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-17T16:40:46+01:00
A) -(8a-4b+5)+(-6a+2b-5)+3(a-b+1)=
=-8a+4b-5-6a+2b-5+3a-3b+3=
=-11a+3b-7

b)3(a+2b-3c)+7(2a-4b+5c)-5(-3a-4b-5c)=
=3a+6b-9c+14a-28b+35c+15a+20b+25c=
=32a-22b+51c

c)-4(-2x+6y+5z)-8(9x+8y-7z)+5(3x-6y+9z)=
=8x-24y-20z-72x-64y+56z+15x-30y+45z=
=-49x-118y+81z

d)(⅔) (3a+6b-12c)+(⅗) (10a-15b+20c)-0,5(16a+24b-36c)=
=2a+4b-8c+6a-9b+12c-8a-12b+18c=
=-17b+22c